Federated Tensor Mining for Secure Industrial Internet of Things - Sheng, Hao (IEEE Xplore, 2020)
In a vertical industry alliance, Internet of Things (IoT) deployed in different smart factories are similar. For example, most automobile manufacturers have the similar assembly lines and IoT surveillance systems. It is common to observe the industrial knowledge using deep learning and data mining methods based on the IoT data. However, some knowledge is not easy to be mined from only one factory’s data because the samples are still few. If multiple factories within an alliance can gather their data together, more knowledge could be mined. However, the key concern of these factories is the data security. Existing matrix based methods can guarantee the data security inside a factory but do not allow the data sharing among factories, and thus their mining performance is poor due to lack of correlation. To address this concern, we propose the novel Federated Tensor Mining (FTM) framework to federate multisource data together for tensor based mining while guaranteeing the security. The key contribution of FTM is that every factory only needs to share its ciphertext data for security issue. And these ciphertext are adequate for tensor based knowledge mining due to its homomorphic attribution. Real-data driven simulations demonstrate that FTM not only mines the same knowledge compared with the plaintext mining, but also be able to defend the attacks from distributed eavesdroppers and centralized hackers. In our typical experiment, compared with the matrix based PPCS, FTM increases up to 24% on mining accuracy.